Usługi rolnicze jako element rolnictwa społecznie zrównoważonego - Urban, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Important elements of the socially sustainable agriculture are services. In Poland they are being dynamically developed during the last period. As a result, the agricultural service sector has under-gone significant changes, of which the crux is the privatization of service centres. In addition, indirect agricultural services, in that the maintenance, repairing and financial services, play the main role in the structure of services provided in the agriculture sector. It is apparent that the number of agricultural centres is diversified in respective voivodships and changes are still being in progress. Further-more, typical agricultural voivodships are particularly well provided with the mechanical and veterinarian services. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 84-90